The European Union and the Arctic - Liu, Nengye; Kirk, Elizabeth A.; Henriksen, Tore (Publications on Ocean Development, 2017)
The European Union and the Arctic examines the roles the EU can and should play in shaping Arctic governance to ensure sustainable development in the Arctic region. Readership: The target audience of the book includes academics, practitioners working in NGOs, international organizations, EU institutions, national governments of Arctic States and non-Arctic States with strong interests in the Arctic.